Selenoproteins in Archaea and Gram-positive bacteria - Stock, Tilmann; Rother, Michael (Biochimica et biophysica acta, 2009)
Selenium is an essential trace element for many organisms by serving important catalytic roles in the form of the 21st co-translationally inserted amino acid selenocysteine. It is mostly found in redox-active proteins in members of all three domains of life and analysis of the ever-increasing number of genome sequences has facilitated identification of the encoded selenoproteins. Available data from biochemical, sequence, and structure analyses indicate that Gram-positive bacteria synthesize and incorporate selenocysteine via the same pathway as enterobacteria. However, recent in vivo studies indicate that selenocysteine-decoding is much less stringent in Gram-positive bacteria than in Escherichia coli. For years, knowledge about the pathway of selenocysteine synthesis in Archaea and Eukarya was only fragmentary, but genetic and biochemical studies guided by analysis of genome sequences of Sec-encoding archaea has not only led to the characterization of the pathways but has also shown that they are principally identical. This review summarizes current knowledge about the metabolic pathways of Archaea and Gram-positive bacteria where selenium is involved, about the known selenoproteins, and about the respective pathways employed in selenoprotein synthesis.